Sustainability Assessment of Intensive Agriculture in Argentina. Focus on Upstream (Emergy) and Downstream (Emissions) Environmental Impacts - Totino, Mariana; Matteucci, Silvia D. (Journal of Environmental Accounting and Management, 2026)
After the Industrial Revolution the agricultural sector was one of the most transformed. The activity releases CO2 and generates a change in land use, advancing on ecosystems with native vegetation, which function as carbon sinks. The model of industrial agriculture is highly dependent on inputs in the form of materials and energy, mainly fossil fuels but there are other hidden constraints that rely on the environmental quality of resources used and the extent of downstream impacts generated by their use in a process, that do not emerge clearly from investigating only material and commercial energy. As a consequence, additional investigation with alternative approaches, like emergy and emission assessment, is needed. In this article the analysis focuses on the emergy assessment and pollutant emissions by soybean production in two Argentine localities with environmental differences, one in the province of Buenos Aires (Rojas) and the other in the Chaco province (Charata). We used an upstream method (Emergy Accounting) and a downstream method (CML2 baseline 2000). Both sites show Renewability smaller than 35%. The total amount of CO2eq emitted in Charata is 0.80 ton/ha/yr and 0.81 ton/ha/yr in Rojas. However, the local conditions, the impact of industrial agriculture is very high. In Chaco region, possible regulations that establish the afforestation of certain areas around soybean crops should be analyzed, to operate not only as carbon sinks but also as barriers for agrochemical drift.